(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article explores the concept of dialects within sociolinguistics, focusing on their definitions, types, social significance, and the attitudes surrounding them. It also discusses how dialects contribute to social identity and inequality, emphasizing why they remain an important area of study in modern linguistics.